2003
DOI: 10.1021/ac026213j
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of MALDI-TOF and FT-MS Techniques for Analysis of Escherichia coli Whole Cells

Abstract: Recently, it has been demonstrated that bacteria can be characterized using whole cells and matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). However, identification of specific bacterial proteins usually requires analysis of cellular fractions or purified extracts. Here, the first application of Fourier transform mass spectrometry (FTMS) to analysis of bacterial proteins directly from whole cells is reported. It is shown that accurate mass MALDI-FTMS can be used to characterize specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 45 publications
5
76
0
Order By: Relevance
“…However, considering that the mass tolerance of 21.38 ppm is known to be a required mass accuracy for the correct assignments of lipid species under the assumption of proton cationization, 10 ppm is not a loose criterion for accurate mass measurements. 16 On the other hand, when a multiple number of lipid candidates existed within a 10 ppm tolerance from the observed monoisotopic mass, only the candidate with the smallest delta-mass (Δm) was selected (Table 1-6). In the case where two closely-spaced peaks existed, both peaks were considered to find lipid candidates as long as these two peaks showed 'A' and 'A+1' isotopic distributions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, considering that the mass tolerance of 21.38 ppm is known to be a required mass accuracy for the correct assignments of lipid species under the assumption of proton cationization, 10 ppm is not a loose criterion for accurate mass measurements. 16 On the other hand, when a multiple number of lipid candidates existed within a 10 ppm tolerance from the observed monoisotopic mass, only the candidate with the smallest delta-mass (Δm) was selected (Table 1-6). In the case where two closely-spaced peaks existed, both peaks were considered to find lipid candidates as long as these two peaks showed 'A' and 'A+1' isotopic distributions.…”
Section: Resultsmentioning
confidence: 99%
“…4,[10][11][12][13][14][15][16][17] Even with the disadvantage of relatively low sensitivity, the direct-infusion ESI-FTMS approach is very easy to implement and also provides a good method to compare the global lipid distributions of two total lipid extracts under inspection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a ribosomal fraction (not whole cells) Arnold and Reilly [29] observed that several ribosomes seem to be present without the expected post-translational modifications, most notably the loss of the C-terminal methionine. Recently, we have confirmed the identity of several ribosomes and their modified forms by accurate mass, high resolution MALDI FTMS analysis of whole cell Escherichia coli [39]. Because the FTMS measurements were done with high accuracy, reliable assignments of the detected ions to ribosomes are possible even without separation from the other cellular proteins.…”
mentioning
confidence: 89%
“…Monoisotopic ion species from five of the previously-identified ribosomal proteins [39] were used as calibrants. The broadband spectra were divided into two mass ranges (m/z 2000 -7000 and m/z 7000 -13000) and the calibrant peaks falling within the ranges used to separately calibrate those subspectral regions.…”
Section: Calibrationmentioning
confidence: 99%